2013
DOI: 10.1037/a0028490
|View full text |Cite
|
Sign up to set email alerts
|

Craving to quit: Psychological models and neurobiological mechanisms of mindfulness training as treatment for addictions.

Abstract: Humans suffer heavily from substance use disorders and other addictions. Despite much effort that has been put into understanding the mechanisms of the addictive process, treatment strategies have remained sub-optimal over the past several decades. Mindfulness training, which is based on ancient Buddhist models of human suffering, has recently shown preliminary efficacy in treating addictions. Interestingly, these early models show remarkable similarity to current models of the addictive process, especially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(128 citation statements)
references
References 152 publications
4
124
0
Order By: Relevance
“…A review of mindfulness training as a treatment for addiction showed a reduction in craving and smoking following training [63]. However, many of the studies were criticized because of lack of randomization and weak controls, and the review called for more rigorous and randomized controlled studies.…”
Section: Mindfulness Meditation and Addictionmentioning
confidence: 99%
“…A review of mindfulness training as a treatment for addiction showed a reduction in craving and smoking following training [63]. However, many of the studies were criticized because of lack of randomization and weak controls, and the review called for more rigorous and randomized controlled studies.…”
Section: Mindfulness Meditation and Addictionmentioning
confidence: 99%
“…Sharp presents the intriguing hypothesis that contemplative training, via its effects on reward pathways in the brain, offers a sustainable and blissful alternative to our habitual patterns of endless thinking and pleasure seeking. This hypothesis is informed by a large body of literature on the nature of addiction and treatment of substance dependence, including how craving, stress, and negative psychological states, such as anxiety and depression, fuel the cycle of suffering (see Brewer, Elwafi, & Davis, 2012). A key point is how meditation creates pleasurable states similar to those generated by traditional reinforcing stimuli using similar neurotransmitters and routes.…”
Section: Resultsmentioning
confidence: 99%
“…A potentially fruitful approach would be to combine meditation with pharmacologic manipulations to test the role of specific neurotransmitter systems in contemplative training. Cross-study findings suggest some overlap in brain regions that are deactivated (and functionally uncoupled) during meditation (e.g., Brewer et al, 2012) and after administration of the selective serotonin agonist psilocybin (Carhart-Harris et al, 2012). These regions in medial prefrontal and posterior cingulate cortex are key nodes in the default mode network, and are alleged to maintain a representation of self versus other, and self in time (Andrews-Hanna, Reidler, Sepulcre, Poulin, & Buckner, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mindfulness training also may be advantageous to treat smokers high in negative urgency because it promotes acceptance of unpleasant experiences rather than attempts to avoid them (Brewer et al, 2013;Zvolensky et al, 2008).…”
Section: Discussionmentioning
confidence: 99%